Treatment challenges in and outside a network setting: Soft tissue sarcomas. Issue 1 (January 2019) - ; Hackl, Monika; Van Eycken, Elizabeth; Henau, Kris; Dimitrova, Nadya; Sekerija, Mario; Dušek, Ladislav; Mägi, Margit; Malila, Nea; Leinonen, Maarit; Velten, Michel; Troussard, Xavier; et al.
Abstract: Patients with soft tissue sarcoma (STS) experienced better outcomes when treated according to existing clinical practice guidelines either at reference institution or dedicated treatment networks. Despite increasing evidence supporting referral to sarcoma specialised units, up to half of patients are not managed according to guidelines, particularly those in the early stage of their disease requiring surgery. Also, criteria to certify expertise of institutions, such as the treatment volume, are debated and health authorities have only recently started identification of these centres and creation of treatment networks in Europe as well as in several countries. This process have important implications for both patient outcomes and innovation of existing treatment strategies through clinical research, making improvement of clinical pathways a priority for health care authorities. This article will discuss issues with management of patients with STS, such as pathological diagnosis and adherence to guidelines, and the definition of referral centres and networks will be illustrated along with existing experiences and population-based data.